Assessment of scientific competencies in secondary school students: exploring the relationships among inquiry, explanations of the physical world, and the design of technological solutions - Angel Edwin Oblitas Silva; Giuliana Orrillo Salazar (Institute of Advanced Engineering and Science, 2026)
Assessing scientific competencies in secondary education requires understanding their structural relationships, yet limited research examines these interrelationships empirically. This study investigated how scientific inquiry, explanation of physical phenomena, and design of technological solutions interact in 165 Peruvian secondary students using partial least squares structural equation modeling (PLS-SEM). Results confirmed that inquiry significantly influences both explanation and design capabilities, while explanation mediates the relationship between inquiry and design. The model demonstrated excellent fit (standardized root mean square residual (SRMR)=0.068, normed fit index (NFI)=0.912)), explaining 67.3% of variance in explanation and 71.8% in design. Findings establish inquiry as the foundational competency for developing explanatory and problem-solving abilities, supporting integrated curriculum design and sequential pedagogical approaches that prioritize inquiry development.